Estudo das propriedades ópticas não lineares de segunda ordem em derivados de chalconas - Oliveira, Klivan Santos (2024)
The search for materials with high nonlinear optical responses has been of great interest, es- pecially organic compounds, which are promising due to their conjugated chains with electron donor and acceptor groups. These characteristics make them strong candidates for applications in photonics and optoelectronics. In this dissertation, we explore the linear and nonlinear optical properties, both computationally and experimentally, of six brominated chalcone compounds: (E)-1-(4-bromophenyl)-3-(p-tolyl)prop-2-en-1-one, (E)-1-(3-bromophenyl)-3-(p-tolyl)prop-2-en-1-one, (E)-1-(4-bromophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one, (E)-1-(3-bromophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one, (E)-1(4bromophenyl)-3(4(dimethylamno)phenyl)prop-2-en-1-one, (E)-1-(3-bromophenyl)-3-(4-(dimethylamino)phenyl)prop-2-en-1-one. The microscopic properties, dipole moment, and first static and dynamic hyperpolarizability were computed using the MOPAC 2016 program, which is based on semi-empirical quantum chemistry and employs the PM7 Hamiltonian. Experimentally, the linear characterization was performed through absorption measurements in the UV-Vis region, determining their optical transparency range. The macroscopic characterization of second harmonic generation (SHG) was conducted using the Kurtz-Perry powder method, revealing good results with SHG relative efficiencies approximately 28 and 22 times greater than KDP. These results indicate that chalcone derivatives exhibit excellent optical properties, making them very promising for applications in photonic devices.